IMPROVING THE METHODOLOGY FOR ENHANCING PEDAGOGICAL OPPORTUNITIES THROUGH THE USE OF ARTIFICIAL INTELLIGENCE IN THE ENGINEERING EDUCATION PROCESS (Eureka Journal of Artificial Intelligence and Data Innovation, 2026)
This article analyzes the issues of enhancing pedagogical opportunities and improving learning efficiency in the process of engineering education through the use of artificial intelligence technologies. It also highlights ways to improve AI-based teaching methodologies, adaptive learning systems, the formation of individual approaches, and the advantages of automating the educational process. The research results demonstrate that artificial intelligence is a significant factor in modernizing engineering education.
Keywords: Artificial Intelligence, Engineering Education, Pedagogical Technologies, Digital Learning, Adaptive Teaching, Innovative Methodology, Competence, Automated Assessment, Learning Efficiency.